SERUM BILIRUBIN LEVEL AT ADMISSION PREDICTS IN-HOSPITAL OUTCOME IN PATIENTS WITH ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION. (June 2018) - Sladojevic, M.; Sladojevic, S.; Bjelica, S.; Oalde, L.S.; Popov, T.; Srdanovic, I.; Stefanovic, M.; Ilic, A.
Abstract : Objective: Serum Total Bilirubin (STB), the final product of the heme catabolic metabolism, has potent anti-oxidative and cytoprotective properties. STB concentration is inversely associated with hypertension, diabetes mellitus, and metabolic syndrome, and has been suggested to be protective against atherosclerosis and coronary artery disease (CAD) under normal conditions, but elevated in patients with ST-Segment Elevation Myocardial Infarction (STEMI) and pressure overload in the Myocardium. Purpose: To evaluate prognostic value of STB during admissionfor in-hospital outcome in patients with STEMI undergoing Primary Percutaneous Coronary Intervention (pPCI). Design and method: A total of 1495 patients with STEMI were admitted to our hospital and submitted to p PCI between December 2008 and December 2011.Exclusion criteria included treatment with thrombolytic drugs in the previous 24 hours, active infections, previously proven systemic inflammatory disease history and liver disease. Results: Most of the patients were male, 65.2% (mean age = 61.47 ± 11.83 years).There was 65% patients with hypertension, 87.3% diabetics, 30.9% with hyperlipidemia and 43% with smoking habits. In-hospital mortality was 8.96% and significantly different with regards to gender (male 12.1% vs. female 7.32%, p = 0.003).There was statistically significant difference of STB mean value between survivors (8.0 μmol/l, range 6.5 – 10.3) and those with a lethal outcome (11.3 μmol/l, range 8.6 – 18.3) - p < 0.0005. Mean value of STB in male was 8.0 μmol/l(6.4 – 10.4) versus 8.8 μmol/l (7.0 – 11.6) in female, (p < 0.0005). Multivariate Cox regression analysis showed that STB was an independent predictor of in-hospital mortality (odds ratio 1.158, 95% confidence interval 1.124 to 1.194, p < 0.005). Receiver operating characteristic curve (ROC) analysis designated STB as a significant indicator of in-hospital mortality (ROC 0.736, p < 0.005), cut-off was 10.25 μmol/l, sensitivity 61.8%, specificity 74.8%.The patients were divided into four quartile groups according to STB value (1st quartile: 5.15–6.5 μmol/l, n = 336 patients; 2nd quartile 6.5–8.2 μmol/l, n = 367 patients;3rd quartile 8.2–10.8 μmol/l, n = 359 patients; 4th quartile 10.8–19.4 μmol/l, n = 368 patients).Subsequent analysis showed markedly increased mortality rate in the 4th quartile group of patients (2.7%, 4.1%, 9.2% and 20.1%, respectively). Conclusions: STB at admission is reliable biomarker of in-hospital outcome prediction in patents with STEMI submitted to pPCI.